Responsive mobile architecture refactoring into mobile HTML5 - Davis, Scott 1971- (O'Reilly, 2015)
"One website for all devices is the mantra of modern 21st century web development. In this video, web design guru Scott Davis offers a concise and practical look at the tools and design approach you need to ensure that your mobile website will look great on any device. Review three basic approaches to mobile app development: HTML 5, Native, and Hybrid; Learn why responsive mobile sites display correctly on any device; Discover proven techniques that solve the mobile-website-multiple-viewport problem; Learn how declarative media queries in CSS3 simplify mobile orientation styling; Discover Twitter Bootstrap, an easy method for creating mobile-friendly websites; Learn HTML5 tricks for popping up a virtual keyboard, tapping a link to dial a phone, and more; Make your mobile HTML5 app look like a native iOS or Android app in airplane mode; Learn local storage techniques that make your mobile app run best when it goes offline; Explore best practices for application caching in mobile apps."--Resource description page.
Title from title screen (viewed November 23, 2015). - Date of publication from resource description page
Keywords: Mobile apps -- Development; Mobile apps -- Design; Applications mobiles; Développement